By the monsters: A failed modernity from Manila Noir, Trese, Alternative Alamat, to Zsazsa Zaturnnah - Elmido, Cecilia Bethina Imperial (Animo Repository, 2019)
Other than the mythic and fantastic nature of monsters in the selected Philippine cultural texts, the Frankenstenian theory from Freud and Foucault is the real monster I want to show. With seven modern short stories from the collections of Manila Noir and Alternative Alamat, and three graphic novels from Trese and Zsazsa Zaturnnah that circulated during 2005 to 2015, I want to explore the hybridity in retelling these Philippine myths in the modern light and read them through the lens of Freud and Foucault. These cultural texts show the failure of modernity in trying to achieve progress through a backward relationship on family and society. It can also be recalled that during the 1992 Philippine presidential elections the local newspapers reported a manananggal terrorizing Manila, to distract people from the rigged election. With this, I seek to answer the following questions: first, why do monsters keep on appearing or regenerating in an urban locale? Why in that form? What does it say about humanity? Second, how do society and culture play a role in the constructed re/presentation of monsters and confession? And in turn how do society and culture respond to monsters and their confessions? Through innuendos of a song, epistolary journals, letters, self-narratives, the characters I chose to illicit confessions from more or less highlight an uncanny double. After their confession breathes life, the motive for a crime is neither revealed nor concealed but indicated or to be executed. Monsters therefore are not just categorized out of difference and abilities but rather by their crimes. At the bottom of these crimes are their haunting confession as of a forgotten culture, which the hybridity becomes a nuisance towards progress as they symbolize the distorted sense of identity. I put weight on the counter-discursive tendencies of the intervention of confession in the Philippine belief of monsters as it also uses the intervention of confessions to produce the very monsters they seek. Of the two collections of short stories, I only selected a few that fits with the following theme. I thematically categorized the selected cultural texts into three, the first as monsters in the city, wherein cultural appropriation to a city-space, such as Manila creates both monster and confession influenced by cosmopolitanism; Second is the political ruling class, from a historical revisionist explanation of the two colonizations the Philippines underwent. One of which is the slave of the first Philippine hero who was responsible for Christianity; Lastly, the transsexuals who the monsters themselves (from the city and political monsters) consider as other. I want to show that in this double-play of reality and fiction in past and present myths, which made society obsessed with the infinite task of extracting the truth from the depths of oneself, rendering psychoanalysis as a form of confession leading towards monstrosity not only as a cultural construct but as a psychological one when monsters blur the imaginary with the real.